Comparison of sizes, morphologies and optical properties of nio nanostructures synthesized using acetate and nitrate anions from nickel salts via hydrothermal method - Pranwadee Kaewmuang (2018)
© 2018, Chiang Mai University. All rights reserved. Porous NiO nanocrystals were synthesized using a hydrothermal method in mediums of different anions from nickel salts, acetate (CH3COO-) and nitrate (NO3-),followed by calcination at 500 °C. Firstly, β-Ni(OH)2powders with a hexagonal structure were formed. Using acetate and nitrate anions, the obtained β-Ni(OH)2powders were composed of thin nanosheets (0.8-2.1 μm in length), and a splinter-like structure self-assembled with longer nanosheets (9.8-24.2 μm), respectively. The difference in the interaction ability between the anions and the β-Ni(OH)2surfaces, affecting the growth behavior of the crystals, was examined using the density functional theory (DFT) method. After calcination, the β-Ni(OH)2turned into porous NiO with a cubic structure but their morphologies were unchanged. The porous NiO with longer nanosheets possessing higher crystallinity and larger surface area provided better UV-Vis absorption ability.